A comparison of ionospheric parameters observed over Ho Chi Minh City with IRI-2007 predictions - Tâm, Đào Ngọc Hạnh; Lan, Hoàng Thái; Vinh, Dương Văn (Vietnam Journal of Earth Sciences, 2014)
This paper presents the results of comparisons the foF2 and TEC observed over Ho Chi Minh City with the values calculated according to the International Reference Ionosphere IRI-2007 in order to evaluate the applicability of the model in forecasting for the equatorial region of Vietnam. The results show a quite consistent of the critical frequencyfoF2 and total electron content TEC in some periods. IRI foF2 values fit well with the observed data for the years before 2007. The standard deviation in these years is about 15%. Only at few of maximum and minimum, the deviations are about 20%. In the years with low solar activities, the IRI foF2 are almost higher than the observed foF2 data. The IRI foF2 values for the first half of 24th solar cycle are bigger than observed foF2, especially during evening. For this period, the adjustment of IRI foF2 must reduce in the range of 25 to 30%. The comparison of the total electron content TEC shows that the phenomenon of decline in the TEC at noon observed over Ho Chi Minh City is highly weak. This phenomenon appeared only in the summer, when the ionization is high. In Solar minimum period, the average minimum TEC observed over Ho Chi Minh City is about 5 tecu, while the IRI TEC value is smaller than 2. Thus, in the period from 0 to 7 pm local time, the IRI TEC value should be calibrated